2008
DOI: 10.1016/j.psyneuen.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolic changes in the prefrontal cortex are associated with HPA axis response to a psychosocial stressor

Abstract: The prefrontal cortex (PFC) has been well known for its role in higher order cognition, affect regulation and social reasoning. Although the precise underpinnings have not been sufficiently described, increasing evidence also supports a prefrontal involvement in the regulation of the hypothalamus-pituitary-adrenal (HPA) axis. Here we investigate the PFC's role in HPA axis regulation during a psychosocial stress exposure in 14 healthy humans. Regional brain metabolism was assessed using positron emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
138
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(157 citation statements)
references
References 53 publications
(72 reference statements)
18
138
0
1
Order By: Relevance
“…Increasing evidence supports that the PFC is important regarding to the HPA axis, since it regulates the HPA response to stress [79], and may also play a role in the glucocorticoid feedback inhibition [80]. In our present study, MIF was predominantly found in astrocytes, and only a smaller proportion could be identified in neurons.…”
Section: Mif Hypothalamic-pituitary-adrenal Axis and Inflammationsupporting
confidence: 59%
“…Increasing evidence supports that the PFC is important regarding to the HPA axis, since it regulates the HPA response to stress [79], and may also play a role in the glucocorticoid feedback inhibition [80]. In our present study, MIF was predominantly found in astrocytes, and only a smaller proportion could be identified in neurons.…”
Section: Mif Hypothalamic-pituitary-adrenal Axis and Inflammationsupporting
confidence: 59%
“…Impairing effects of stress on WM performance have mainly been ascribed to GC actions in the PFC (Lupien and Lepage, 2001). The PFC is densely packed with GRs and involved in regulating stress-induced HPA axis activity (Diorio et al, 1993;Lupien and Lepage, 2001;Sullivan and Gratton, 2002;Kern et al, 2008;Cerqueira et al, 2008). Both animal and human studies have shown associations between deficits in prefrontal cognitive functions and HPA axis dysregulations (Mizoguchi et al, 2004;Liberzon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sesay, Tanaka, Ueno, Lecaroz, and De Beaufort, 2000) associated with chewing gum. Additionally, Kern, Oakes, Stone, McAuliff, Kirschbaum, and Davidson (2008) have demonstrated that the increase in glucose metabolism in the rostral medial prefrontal cortex (areas BA9 and BA10) is associated with decreases in salivary cortisol concentrations following the Trier Social Stress task. On the basis of these findings, one might speculate that the increased cerebral blood flow (e.g.…”
Section: Introductionmentioning
confidence: 99%